Pelatihan Membuat Media Serbaneka Berbasis Digital dalam Penguatan Kreativitas P5 di Sekolah Dasar - Ema Butsi Prihastari; Oktiana Handini; Miftahul Avi Syamsyiah (Perkumpulan Kualitama Edukatika Indonesia, 2026)
The objectives of the Community Service program are to impart knowledge and skills in creating digital-based serbaneka media, and to enhance the creativity dimension in the Merdeka curriculum at the primary school level in Surakarta City. The program employs three methods: a) problem approach, b) activity planning, and c) output preparation. The target participants are elementary school teachers partnered with FKIP Slamet Riyadi University. This program assumes significance as it endeavors to provide practicality and efficacy in implementing the creative dimension through digital-based serbaneka media. Additionally, it aims to explore the potential and effective utilization of serbaneka media in teaching the Merdeka curriculum. This training offers a possible solution to teachers' concerns about time constraints. In fact, an analysis of the program's activities revealed that over 75% of the teachers reported experiencing the benefits of implementing these activities. It is recommended to consider the integration of Artificial Intelligence in the development of learning media for fostering the creativity dimension among elementary school students.